QVANDOQVE BONVS DORMITAT HOMERVS. ERRORES Y FALSEDAD EN ALGUNOS AUTORES GRIEGOS - Macía Aparicio, Luis M. (Myrtia, 2003)
In the works of certain Greek authors one may find, more or less visible, mistakes, negligences and incoherences. In some other occasions, what those authors intend to express and what they really offer seem to be contradictory; both faults, either being willing or not, attempt against the beauty of the works and against the credibility of their content. The aim of this essay is both to offer examples of this kind, and to proceed to a critical analysis, an appraisal and an explanation of the issue.